KOMPARASI METODOLOGI DAN CORAK PENAFSIRAN DALAM KITAB AL-ASAS FI AL-TAFSIR DAN KITAB AL-BAHR AL-MUHITH - Risko Ari Saputra; Evi Aulia; Ahmad Dasuki (Yayasan Panca Bakti Wiyata Pangandaran, 2026)
This study examines a comparative analysis of the methodology and interpretive orientations employed in Al-Asas fi al-Tafsir by Sa‘id Hawwa and Al-Bahr al-Muhith by Abu Hayyan al-Andalusi. These two Qur’anic commentaries represent different periods and tendencies within the tradition of Qur’anic exegesis, namely classical and modern tafsir. The study aims to identify the interpretive methodologies adopted by each exegete, explore their dominant interpretive orientations, and analyze the similarities and differences between them. This research adopts a qualitative approach through library research. The primary sources consist of Al-Asas fi al-Tafsir and Al-Bahr al-Muhith, while secondary sources include relevant books and scholarly articles. Data analysis is conducted using a descriptive-comparative method by examining the methodologies, interpretive characteristics, and selected examples of exegesis found in both works. The findings reveal that Sa‘id Hawwa employs a tahlili method with a strong emphasis on the thematic unity of the Qur’an (al-wahdah al-qur’aniyyah), alongside a tarbawi, da‘wah-oriented, and spiritual interpretive approach that is responsive to modern challenges. In contrast, Abu Hayyan al-Andalusi applies a tahlili method characterized by a dominant lughawi orientation, particularly in his detailed analysis of Arabic grammar (nahw), morphology (sarf), and rhetoric (balaghah), while demonstrating caution toward scientific interpretations of the Qur’an. These methodological and interpretive differences indicate that Qur’anic exegesis is closely shaped by the intellectual context and the needs of the Muslim community in each historical period. This study is expected to contribute to the field of Qur’anic studies by enriching scholarly discourse on the dynamics of exegetical methodology from the classical to the modern era.